Resuspension of trace explosive particle residues by planar impinging jet: Effects of exposure duration and wall shear stress. (January 2023) - Kottapalli, Kalyan; Murali, Harikrishnan; Song, Guanyu; Fillingham, Patrick; Novosselov, Igor
Abstract: Aerodynamic particle resuspension is important in many practical applications, such as surface cleaning, understanding particle fate in the environment, and surface sampling. In practical application, the probability of particle resuspension from the surface depends on several parameters, such as particle size, morphology, chemical composition, surface properties, environmental and flow conditions. The wall shear stress ( τ w ) links fluid motion and forces acting on the particle and can be used to characterize particle resuspension. The literature reports that the resuspension rates decay as 1/t at long exposure times; however, the effect of very short exposures to aerodynamic forces on the resuspension of irregular microparticles has not been characterized. This work examines the effect of τ w and exposure duration utilizing planar jet pulses. We evaluated resuspension silica spheres and irregular Trimethylenetrinitramine (RDX) microparticles from a smooth glass surface with a 10–100 ms pulse duration and extended exposure (60 s) for the same wall shear stresses. Reducing the jet duration shows that the removal rate is inversely proportional to exposure time; the trend is more visible at lower τ w . At higher shear stresses, up to 80% of particles are removed in the first 10 ms of exposure to aerodynamic force. Graphical abstract: Image 1 Highlights: The method allows examining the particle reaerosolization as a function of jet duration. 80% of the particles are removed in the first 10 ms of exposure to aerodynamic load. Reaerosolization increases with wall shear stress; the rates for energetic residues are quantified. As the wall shear stress decays from the stagnation point, the particle removal decreases.